A Comprehensive Study on the Effect of BaSO4 on Gamma-Ray Shielding Properties of B2O3-CaO-Na2O-SiO2 Glass System, a Comparative Evaluation Using Phy-X / PSD and XMuDat Program - Wattar, Hala (University of Thi-Qar Journal of Science, 2025)
The mass attenuation coefficient (μm), linear attenuation coefficients (μ), half value layer (HVL), mean free path (MFP), total atomic cross section (ACS), total electronic cross section (ECS), and effective atomic number (Zeff) are determined in this research because they are the most important radiation attenuation coefficients and play a significant role in the fields of radiography, radiotherapy, and prevention of ionizing radiation. Gamma ray shielding properties of silicate glasses (10B2O3-10CaO-20Na2O-(60- x) SiO2- x BaSO4) with (0 ≤ x ≤40 wt%) have been achieved. The attenuation coefficients for gamma rays were calculated theoretically with the help of the Phy-x program, and then these values ​​were compared with the results obtained using the XMuDat program. Variations of shielding parameters are discussed for the effect of BaSO4 addition into the glasses and photon energy of range from (0.003-3) MeV including the radioactive sources 22Na, 60Co, 131I, and 137Cs. Glass with the highest doping concentration achieved the optimum values for μm, μ, and Zeff. The lowest values of MFP and HVL for the glasses were observed for intermediate energies of gamma photons. The computed values of various attenuation coefficients for gamma rays like μm, μ, HVL MFP, ACS, ECS, and Zeff derived from the XMuDat program were in good agreement with the theoretical values resultant using the Phy-X program. The proposed glass system of the form (10B2O3-10CaO-20Na2O-20SiO2-40BaSO4) may be useful for many shielding applications.